Assessing data quality in survey with healthcare providers on COVID-19 and the measures for improving - Srivastava, Ambey Kumar; Gupt, Rajan Kumar; Bhargava, Ruchi; Singh, Rajesh Ranjan; Ahmed, Shoyab (Open Science Journal, 2021)
Background: Social surveys have also been transformed with the advancements in research methods. However, only through appropriate methods, proper planning and procedures the data quality can be ensured. Aim: The aim of the current research is to present the measures taken up in doing survey with healthcare providers of primary health care facilities during the time of COVID-19 and to assess the data quality. Method: The survey was conducted with all 280 medical and paramedical staff in 24 primary healthcare centers of government to understand the preparedness of primary health care facilities in terms of providing a safe working environment to healthcare providers and to prevent the spread of infection while discharging duties during COVID-19. The study used mix mode of data collection by administering telephonic and self-administered questionnaire. It is a descriptive study based on review of secondary literature and the different measures adopted in the survey to ensure data quality. Result: The variation found in responses to questions related to training, personal fears, challenges and coping mechanism was low, when asked differently in telephonic and self-administered questionnaire. It shows that the measures taken in conducting survey through mix mode of data collection at the time of COVID-19 were effective in overcoming the data quality challenges of COVID-19 to conduct face-to-face study and maintaining data quality of the survey. Conclusion: It can be concluded that proper planning, preparations and precautions were effective in ascertaining the data quality.